Impact on genitourinary function and quality of life following focal irreversible electroporation of different prostate segments - Scheltema, Matthijs J. (Diagn Interv Radiol, 2018)
PURPOSE: We aimed to evaluate the genitourinary function and quality of life (QoL) following the ablation of different prostate segments with irreversible electroporation (IRE) for localized prostate cancer (PCa). METHODS: Sixty patients who received primary focal IRE for organ-confined PCa were recruited for this study. Patients were evaluated for genitourinary function and QoL per prostate segment treated (anterior vs. posterior, apex vs. base vs. apex-to-base, unilateral vs. bilateral). IRE system settings and patient characteristics were compared between patients with preserved vs. those with impaired erectile function and urinary continence. Data were prospectively collected at baseline, 3, 6, and 12 months using the expanded prostate cancer index composite, American Urological Association symptom score, SF-12 physical and mental component summary surveys. Difference over time within segments per questionnaire was evaluated using the Wilcoxon’s signed rank test. Outcome differences between segments were assessed using covariance models. Baseline measurements included questionnaire scores, age, and prostate volume. RESULTS: There were no statistically significant changes over time for overall urinary (P = 0.07–0.89), bowel (P = 0.06–0.79), physical (P = 0.18–0.71) and mental (P = 0.45–0.94) QoL scores within each segment. Deterioration of sexual function scores was observed at 6 months within each segment (P = 0.001–0.16). There were no statistically significant differences in QoL scores between prostate segments (P = 0.08–0.97). Older patients or those with poor baseline sexual function at time of treatment were associated with a greater risk of developing erectile dysfunction. CONCLUSION: IRE is a feasible modality for all prostate segments without any significantly different effect on the QoL outcomes. Older patients and those with poor sexual function need to be counseled regarding the risk of erectile dysfunction.